Assist those most in need, or most of those in need? The challenge of allocative efficiency for aid effectiveness - Elena Pietschmann (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Against the current backdrop of declining aid budgets, the efficient allocation of aid is of crucial importance for its effectiveness. Allocative efficiency (aid is allocated where it has the largest impact) has become at least as important as operational efficiency (aid is used in a way that maximises results per unit of spending). Donors have committed in international forums in Paris (2005), Accra (2008), and Busan (2011) to improve allocative efficiency by increasing coordination among donors and avoiding duplication. However, implementation of this aspect of the aid effectiveness agenda has been slow and is currently stalling. Moreover, it remains unclear what principles should guide aid allocation across recipients and sectors. In principle, cross-country aid allocation can be based either on recipients' needs or on performance. There are valid theoretical arguments for both of these conceptual approaches, and the empirical evidence is insufficient to assess their relative merit. While needs-based approaches would direct aid mainly to the neediest countries, performance- based approaches would target well-governed countries where aid is more likely to reach many people in need. Donors face difficult choices because institutional quality tends to be lower in the neediest countries. Also, many people in need nowadays live in middle-income countries but these are not the countries where those most in need live. There is often a trade-off between assisting many people in need and those most in need, making it difficult to identify an optimal allocation under both approaches simultaneously. In practice, donors allocate according to many different criteria, including geostrategic interests that divert aid from where it has the highest impact. Moreover, lack of coordination leads donors to concentrate on the same countries while neglecting other recipients that also have relatively high needs and performance. Thus, while trade-offs and lack of evidence make it difficult to define clear guidelines for an “optimal allocation”, inefficiencies in overall aid allocation can be identified. Multilateral donors whose allocations are presumably less biased could partly balance overall aid allocation by directing larger shares of aid to bilaterally underfunded countries. But it is also important to improve coordination and transparency in allocations by all donors. The Global Partnership for Effective Development Cooperation (GPEDC), which brings together all main development actors, is in a good position to engage in overcoming the political obstacles that hinder donor coordination. Coordination will be insufficient and difficult to achieve if geostrategic interests continue to influence aid allocations, but increasing transparency is a good step forward. Donors should adopt transparent allocation formulas based on performance and/or needs and factor in each other's allocations in their own formulas. The Organisation for Economic Co-operation and Development (OECD) could play an important role in fostering this ex-ante coordination by continuing to push for a full disclosure of donor-specific indicative forward spending plans. Moreover, the Development Assistance Committee (DAC) peer review could focus more on allocation decisions in its assessment of bilateral donors' development cooperation systems, increasing the peer pressure on its members to adopt transparent allocation criteria
Keywords: 330